The Effectiveness of the 'Stop Pesan Sensi' Program in Reducing Bullying in Indonesian Elementary Schools: A Collaborative Approach Among Teachers, Parents, and Students - Puspitasari, Wiwin; Muhimmah, Hitta Alfi; Nursalim, Mochamad (Papanda Publisher, 2025)
Bullying in elementary schools remains a significant challenge that affects students' psychological well-being and academic performance. This study examines the implementation and effectiveness of the